2022
DOI: 10.3389/fneur.2022.909437
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes of Frontal Areas in Male Individuals With HIV: A Deformation-Based Morphometry Analysis

Abstract: ObjectivePrevious studies on HIV-infected (HIV+) individuals have revealed brain structural alterations underlying HIV-associated neurocognitive disorders. Most studies have adopted the widely used voxel-based morphological analysis of T1-weighted images or tracked-based analysis of diffusion tensor images. In this study, we investigated the HIV-related morphological changes using the deformation-based morphometry (DBM) analysis of T1-weighted images, which is another useful tool with high regional sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…We further focused on the right BG following the previous study [ 31 ]. Our previous studies on the same population also found that, there were more group differences in the right hemisphere, including disrupted resting-state functional connectivity [ 36 ] and morphological changes [ 37 ], not only between PLWH and normal subjects [ 36 , 37 ], but also between subgroups within PLWH [ 36 ]. Based on these right-lateralized findings, we speculated that HIV or HAND related metabolic changes in this cohort were more probable to be detected in the right hemisphere.…”
Section: Introductionmentioning
confidence: 93%
“…We further focused on the right BG following the previous study [ 31 ]. Our previous studies on the same population also found that, there were more group differences in the right hemisphere, including disrupted resting-state functional connectivity [ 36 ] and morphological changes [ 37 ], not only between PLWH and normal subjects [ 36 , 37 ], but also between subgroups within PLWH [ 36 ]. Based on these right-lateralized findings, we speculated that HIV or HAND related metabolic changes in this cohort were more probable to be detected in the right hemisphere.…”
Section: Introductionmentioning
confidence: 93%